Entrevue guidée avec Antoine Laville - Esther Cloutier; Raymond Baril; Daniel Drolet (Perspectives Interdisciplinaires sur le Travail et la Santé)
In this inaugural edition of the Pioneers column in PISTES, we present an interview with physician Antoine Laville, who has made an active contribution to the development of ergonomics in the French-speaking world. He began his research career in 1962 with a look at the impact of working conditions on workers in the Occupational Physiology Laboratory at CNAM. Since 1990 he has been Director of the doctoral program in ergonomics at the École pratique des hautes etudes (EPHE) in Paris, and in 1991 he became one of the two founding members of the Age and Population Research and Study Centre, known by its French acronym CREAPT. PISTES met with him before his imminent retirement, giving readers an opportunity to learn more about his career and hear some of the thoughts he most generously shared to us.